Application of Coding Learning in Early Childhood (5-6 years) with ScratchJr Application - Raeh Niken Baghiroh; Rahmawati, Yuli; Tarwiyah Adi Sam, Tuti (Exploration in Early Childhood Research, 2024)
The rapid advancement of digital technology makes people familiar with coding skills. Coding can simply be interpreted as the way humans communicate with computers by creating software or applications that are useful in problem solving. This study aims to describe how coding learning is applied in early childhood (5-6 years) at Loop Academy. This research uses a qualitative descriptive approach with a case study design. The subject of the study was a coding instructor and CEO of Loop Academy. Data collection using in-depth interview methods, observation, and documentation studies. Data analysis techniques are carried out by means of data condensation, data display, drawing conclusions, and verification. The results of the study provide an illustration that coding learning in early childhood (5-6 years) uses Scra tchJr. The ScratchJr application allows children to engage in the creation of creative stories, animations, and even interactive games, as well as having creative problem-solving, logical reasoning, support collaboration, and create an interactive learning environment that children can take advantage of.